What changes in relationship with their children do primary caregivers perceive as having occured since being involved in a centre-based early intervention music therapy programme? : a thesis presented to fulfill the requirements for the degree of Master of Music Therapy at Massey University - Archer, Christine A (Massey University, 2004)
The purpose of the present study was to examine how participation in music therapy (MT) influenced the carer-child relationship when both carer and child were involved in group and individual MT as part of an early intervention (EI) programme . The study took place at the Wellington Early [ntervention Trust (WEIT), a centre catering for children with significant disabilities, and their families. Four primary caregivers involved in this centre-based, multi-disciplinary EI programme involving both weekly group and individual MT were interviewed. Two carers had more than twenty MT sessions, while two carers were interviewed after only ten sessions. Analysis of the transcripts comparing the carers' responses revealed a number of common features: First, a marked change was observed in the nature and quality of carer-child interactions consequent on participation in a specific EI programme. All four participants4 spoke positively about their involvement with their children in both the group and individual MT sessions. Second, not only did the carers report positive gains in their children's overall development as a result of their experience of MT in EI, but all four participants reported how they now used music as part of their every day lives as a tool to encourage and maintain positive carer-child interactive experiences. Third, each carer became more aware and confident in how to use their own voice and body language to engage in successful interactions with their child. This study found that the interactions between child and caregiver changed in nature and quality since being involved in MT in EI. Their relationship with their child had strengthened with positive results for the child's developmental objectives.
Keywords: Music therapy for children; Music therapy